The National Agricultural Strike: The Paradoxes of Political Action for Social Change - Arias Fernandez, Monica (2016)
The National Agricultural Strike in Colombia as a political event was a social mobilization that brought into question the margins of political action. It was an event that cannot be reduced only to the actors implicated and causes but brought into focus the precarious condition of agricultural production in Colombia: the concentration of land and agricultural production, questions of local security and the model of economic development. This strike is analyzed drawing upon the thought of Gilles Deleuze and Felix Guattari, who develop a number of concepts that serve to analyze the ways in which resistance and social mobilization occupy an inherent space inside the exercise of state power. From the question about the conditions that make social change possible and the place of social mobilization within this panorama, this study develops a critical take that allows problematizing the role of society in the construction of alternatives for social change.